Software educativo didáctico para el aprendizaje de la asignatura Informática. - Muguercia Bles, Alcides; Luna Negret, Yirsa; Valenciano, Vivian Benito; de la Torre Vega, Gertrudis (MEDISAN, 2026)
It was decided to elaborate a didactic educational software for the learning of the Computer science subject, as a solution to the failures detected in the urdergraduate and postgraduate students of the subject Health Information Systems. This software was designed with the tool Chreasoft 3.1, and it was structured in modules that link texts, images and videos, which livens up and motivates learning and it speeds up the study of the contents of the subject. Finally a compatible computer product was achieved with similar operating systems for Windows and Linux, contributing to the teaching-learning process as it makes possible the constant development of students and professors.